HAL SEPELE SEBAGAI OBJEK KARYA SENI LUKIS - JONI MUKRIZAL, Drs. Ady Rosa, M.Sn, Drs. Idran Wakidi (Serupa The Journal of Art Education, 2014)
Trivial case is one of the foundation to get to a better direction. The purpose of this study is: to express themselves in paintings, Expanding knowledge, and message about something to overlooked problems. This technique of 7this study is transparently with the cultivation of contemporary style and flow that has freedom in painting. The conclusion of this study is the issue or problem should not be considered as trivial case/ frivolous, because trivial case is also has a great impact in life. This feelings which can be visualized in painting as something that we can contemplated to learning process for writers and other human. Keyword : trivial case, work painting